Electroweak corrections in the 2HDM for neutral scalar Higgs-boson production through gluon fusion - Laura Jenniches; Christian Sturm; Sandro Uccirati (Journal of High Energy Physics, 2018)
Abstract We have computed the two-loop, electroweak corrections to the production of a light and a heavy neutral, scalar Higgs-boson through the important gluon fusion process in the Two-Higgs-Doublet Model. We provide our results in various renormalization schemes for different scenarios and benchmark points, which will be valuable for experimental studies at the LHC. We describe the technicalities of our two-loop calculation and augment it by a phenomenological discussion. Our results are also applicable to the gluonic neutral, scalar Higgs-boson decays.